'Boundless informant': Insecurity in the age of ubiquitous surveillance. (September 2017) - Masco, Joseph
This article considers how technological revolution in digital technologies is effecting scholarship, activism, and privacy in the United States. Examining the revelations of Edward Snowden about National Security Agency domestic programs, it considers the status of the security 'file' and the role of anthropology in engaging a world without privacy.